STIPULATION OF THE COST OF FISH SALES IN PT. SATU ENAM DELAPAN BENOA - Saputra, I Made Valentino Rossi; Maheswari, Anak Agung Istri Agung (LPPM Univ. Ibn Khaldun Bogor, 2022)
PT. Satu Enam Delapan is a company that engages in the frozen fish industry, especially tuna, and several other types of fish, through export sales. The company doesn’t catch fish directly at sea to obtain raw materials, but by buying from fishermen and traders who have become permanent fish suppliers. Furthermore, the fish raw material has a fillet process at the company by removing certain parts such as the bones, which will affect the Cost of Goods Sold. Therefore, the determination of Cost of Goods Sold here is an important point for the company and must be determined precisely, because of the many types of products and several considerations such as the routine of buying fish, the difference in the price of each kilogram for the same type of fish, and the change on fish weight due to the production process. That way the Average method used by the company and the perpetual inventory recording method is easier and more effective than other methods, recording inventory perpetually will make it easier for companies to see a fish stock through existing inventory cards, besides that it also provides convenience and effectiveness in making Cost of Goods Sold